Antimicrobial susceptibility of isolated pathogens from patients with contact lens-related bacterial keratitis in Crete, Greece: A ten-year analysis. Issue 4 (August 2021) - Spernovasilis, Nikolaos; Maraki, Sofia; Kokorakis, Evangelos; Kofteridis, Diamantis; Tsilimbaris, Miltiadis; Siganos, Charalampos; Samonis, George
Abstract: Purpose: To evaluate the bacterial spectrum and antimicrobial susceptibilities of pathogens isolated from contact lens-related bacterial keratitis cases in a large academic Greek hospital. Methods: All adult patients with positive corneal scrapings or contact lens culture between 2007 and 2016 at the University Hospital of Heraklion, Greece, were retrospectively identified through a local microbiology database and their medical records were reviewed. Results: A total of 240 isolates were recovered from 131 patients with culture-proven contact lens-associated bacterial keratitis. The most common microorganism identified was Serratia marcescens (17.1% of total isolates), followed by Pseudomonas aeruginosa, Klebsiella spp. and coagulase-negative staphylococci (CoNS). Rates of aztreonam-resistant P. aeruginosa and erythromycin-resistant CoNS decreased in recent years, while the decrease in oxacillin-resistant CoNS was statistically significant ( p =0.009). More than 90% of the isolated organisms ( S. marcescens, P. aeruginosa, Klebsiella spp. and CoNS) were susceptible to ciprofloxacin or gentamicin. Conclusion: Gram-negative microorganisms are the most common causative pathogens of contact lens-related keratitis in the region of Crete. Topical antibacterials containing quinolones or gentamicin represent an effective empirical treatment for the majority of the cases. This is quite encouraging, considering that the present study was conducted in a country characterised by high antimicrobial resistance rates. However, culture-driven antimicrobial treatment is mandatory for this sight-threatening infection.